IDENTIFICATION OF HYDROTHERMAL DISTRIBUTIONS USING THE WENNER-SCHLUMBERGER CONFIGURATION GEOELECTRIC METHOD IN LEMEU VILLAGE, LEBONG REGENCY, BENGKULU - Kausari, Alfata; Rafly, Tegar Al; Muammar, Zaky; Refrizon, Refrizon; Halauddin, Halauddin; Suhendra, Suhendra; Sahputra, Rio; Raihana, Hana; Rahmat, Andre (Universitas Mataram, 2024)
The hot spring pool, Lemeu Village, Lebong Regency, is one of the geothermal fields. This research aims to identify the study area's geothermal potential and lithology. This is illustrated by the correlation method of resistivity and electrical conductivity values of rocks based on geoelectric measurements. This research uses the Wenner-Schlumberger configuration geoelectric method, as many as four tracks spread around the hot spring hill with a length of 480 meters, which are used to see variations in resistivity values that can indicate the presence of hydrothermal potential. The result is a 2D Resistivity model processed with Res2DinvX32 software. Based on the interpretation results, the subsurface rock lithology in each track is relatively similar in color, texture, grain size, and composition because it is around the hill. The Hulusimpang formation consists of clay, silty sand, tuff, andesite, basalt, and granite. Hydrothermal is found on lines 2 and 4 with resistivity values of 7.3 and 10.1 Î©m at a depth of 26 meters. Geothermal potential in the research area is divided into several temperature categories; some have low, medium, and high temperatures. In the research area, tracks 1 and 3 have low temperatures.